The Role of Arabic Teachers in Developing Students Arabic Language Skills at Elementary School: Peran Guru Bahasa Arab Dalam Mengembangkan Kemampuan Berbahasa Arab Siswa MI - Mar'atus Sholihah; Nur Maslikhatun Nisak (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study was to analyze the role of the Arabic language teacher at MI Muhammadiyah 16 Pondok Karangasem Paciran Lamongan and to analyze the development of students' Arabic skills at MI Muhammadiyah 16 Pondok Pesantren Karangasem Paciran Lamongan. This research method uses a qualitative descriptive method with primary data sources in the form of interviews with teachers of MI Muhammadiyah 16 Pondok Pesantren Karangasem Paciran Lamongan. From this research, it was found that the teacher of MI Muhammadiyah 16 Pondok Pesantren Karangasem Paciran Lamongan had performed his role well. However, the method used by the teacher during learning is considered inappropriate if the use of singing to memorize mufradat is generalized to students in grades 1-6. The results of the final semester exams for students in grades 1-6 are above the minimum completeness criteria (KKM), but when viewed from the historical value that MI Muhammadiyah 16 Pondok Pesantren Karangasem Paciran Lamongan is located in a cottage environment and is under the auspices of the Muhammadiyah college, the resulting score unsatisfactory students. The scores obtained by male students were lower than those of female students. So it is necessary to upgrade the method.